Direct, Biomimetic Synthesis of (+)-Artemone via a Stereoselective, Organocatalytic Cyclization - Nacsa, Eric D.; Fielder, Brian C.; Wetzler, Shannon P.; Srisuknimit, Veerasak; Litz, Jonathan P.; Van Vleet, Mary J.; Quach, Kim; Vosburg, David A. (Synthesis, 2015)
We present a four-step synthesis of (+)-artemone from (–)-linalool, featuring iminium organocatalysis of a doubly diastereoselective conjugate addition reaction. The strategy follows a proposed biosynthetic pathway, rapidly generates stereochemical complexity, uses no protecting groups, and minimizes redox manipulations.
Keywords: natural products; cyclization; terpenoids; total synthesis; stereoselective synthesis; green chemistry; organocatalysis; biomimetic synthesis